ADVANTAGES OF CRITERIA-BASED ASSESSMENT OF STUDENTS' ACADEMIC ACHIEVEMENTS IN TERMS OF UPDATING THE CONTENT OF EDUCATION - Лазоренко, Людмила (Modern engineering and innovative technologies, 2022)
The evolution of updating the content of education imposes new requirements on teaching within the framework of the competency-based approach to teaching. Contemporizing the structure and content of education is to overcome the traditional style of learni